2021
DOI: 10.31557/apjcb.2021.6.2.123-132
|View full text |Cite
|
Sign up to set email alerts
|

Real-world Treatment Patterns in Patients with EGFR Mutation-positive NSCLC Receiving a First-Line, First- or Second-generation EGFR Tyrosine Kinase Inhibitor in South Korea and Taiwan

Abstract: Introduction: The preferred first-line (1L) treatment for epidermal growth factor receptor (EGFR) mutation-positive (EGFRm) advanced/metastatic non-small lung cancer (NSCLC) are EGFR-tyrosine kinase inhibitors (TKIs). However, most patients treated with 1L first- or second-generation (1G/2G) EGFR-TKIs acquire resistance; the EGFR T790M mutation is observed in ~30–50% of patients. We report real-world NSCLC treatment and T790M testing patterns in South Korea and Taiwan. Methods: Retrospective medical record rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…These include the open-label, randomised, Phase 3 LUX-Lung 6 study, which compared second-generation EGFR-TKI afatinib with the gemcitabine plus cisplatin In this study, afatinib was the most frequently prescribed EGFR-TKI in the 1L setting. A similar observation was made in the real-world study by Lee et al 2021 in a cohort of 235 patients from South Korea treated between January 2015 and December 2017 [18]. However, these findings contrast from real-world observations in the USA of 782 patients who initiated 1L treatment between January 2016 and July 2019, for whom erlotinib was the most common 1L treatment [19].…”
Section: Discussionsupporting
confidence: 52%
“…These include the open-label, randomised, Phase 3 LUX-Lung 6 study, which compared second-generation EGFR-TKI afatinib with the gemcitabine plus cisplatin In this study, afatinib was the most frequently prescribed EGFR-TKI in the 1L setting. A similar observation was made in the real-world study by Lee et al 2021 in a cohort of 235 patients from South Korea treated between January 2015 and December 2017 [18]. However, these findings contrast from real-world observations in the USA of 782 patients who initiated 1L treatment between January 2016 and July 2019, for whom erlotinib was the most common 1L treatment [19].…”
Section: Discussionsupporting
confidence: 52%
“…This study revealed that the efficacy and safety profile of osimertinib were in line with the results of the AURA3 trial. Osimertinib has been approved as a second or more line setting in EGFR T790M-positive NSCLC patients since December 2017 [ 14 ]. However, there have only been a limited number of real-world studies investigating the efficacy and safety of osimertinib in the Asian population.…”
Section: Introductionmentioning
confidence: 99%
“…The ability to differentiate between a malignant and a noncancerous cell is essential to intervene in treating cancer cell progression so that the normal cells remain undisturbed. Hence, current research efforts mainly focus on developing targeted therapies on key molecules elaborate in tumor proliferation and survival (Citri and Yarden, 2006;Du et al, 2021;Lee et al, 2021). Epidermal growth factor receptors (EGFR) is one such target that has been successful in curing solid tumors (Viswanathan et al, 2019;Abeer et al, 2021;Zhang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%